EVA® - VALOR ECONÔMICO AGREGADO - Backes, Jorge André (2009)
The present study turns on the theme EVA® Economic Value Added, a measure of managerial valuation, considered for many specialists as the true key for the creation of the wealth. The study intends to approach the aspects related EVA®, beginning for its concept, historical, calculation forms, advantages and disadvantages, finally, to provide an including vision that facilitates to the interested an excellent theoretical base.